Qumran and the Origins of Johannine Language and Symbolism - Mburu, Elizabeth W. (T&T Clark, 2010)
This work sets out to demonstrate that the sectarian Qumran document The Rule of the Community, provides linguistic clues which illuminate our understanding of how the author of the Fourth Gospel used truth terminology and expected it to be understood. It establishes that there are significant linguistic similarities shared by these two corpora. While these may be attributed to a development of the common tradition shared by both, as well as the influence ideology, the semantic continuity with the Rule of the Community makes it likely that the author of the Fourth Gospel was familiar with the mode of thought represented in the linguistic matrix of the Qumran literature and that he followed this in articulating his ideas in certain parts of his Gospel.